Mediastinal hydatid cyst: a case report - Msougar, Yassine (BioMed Central, 2013)
INTRODUCTION: Mediastinal localization of hydatidosis is very rare even in endemic areas. The diagnosis is based on typical clinical and radiological criteria. CASE PRESENTATION: We report a case of a mediastinal location of hydatidosis in a 60-year-old Arab man admitted for chest pain. The chest radiograph showed a rounded and homogeneous opacity. Computed tomography showed a right mediastinal cyst, without other thoracic or abdominal sites. Through a posterolateral thoracotomy, we found a cystic mass in the posterior mediastinum. The patient received a cystectomy with medical treatment based on albendazole. He improved a few weeks later. CONCLUSION: Mediastinal cysts remain rare, even in endemic countries, which makes initial diagnosis difficult. Our observation shows the importance of keeping this diagnosis in mind when a patient presents with signs of mediastinal compression.